Present status of fish availability in Ruhul Beel, northern Bangladesh (Journal of Bio-Science, 2018)
This study was conducted in Ruhul Beel, Pabna, northern area of Bangladesh to know the availability of different fish species. Samples were collected fortnightly from the fishermen catch captured in different points of the Beel during January to December, 2013. During this study a total of 37 fish species under 9 orders and 19 families were recorded from the study area. Cypriniformes was the most dominant order constituting 32.43% of the total fish populations followed by the Siluriformes (27.02%), Perciformes (21.62%), Channiformes (5.4%) and Clupeiformes (2.7%). On the contrary, Beloniformes, Cyprinodontiformes, Osteoglossiformes and Tetraodontiformes were the least numerous orders constituting only 2.71% each of the total fish populations. Among the available fish species, 37.84% were very rare, 35.14% were rare, and 21.61% were found throughout the year in a small amount while only 5.41% were available throughout the year in a large amount. About half of the fish species available in the Ruhul Beel is threatened to extinct according to IUCN Bangladesh. The results of this study will provide important baseline data on availability of fish species, which will be helpful for the sustainable management and conservation of fisheries diversity in the Ruhul Beel as well as in the open water- bodies of Bangladesh.J. bio-sci. 25: 39-44, 2017